Uterus bicornis unicollis; occurrence of consecutive viable pregnancies in separate horns (2007)
A case of two-consecutive viable pregnancies in separate horns of bicornuate unicollis uterus of a Nigerian is presented. The problem of misdiagnosis associated with the anomaly is noted. This case further demonstrates that women with such anomaly may not have unhindered reproductive carrier and antenatal care will improve their chance